Intersecting sex and gender diversity with sexual rights for people living with dementia in later life: an example of developing a learning framework for policy and practice - Hafford-Letchfield, Trish (Frontiers in Dementia, 2024)
The proliferation of literature on dementia over the last decade has begun to address the experience of LGBTQ+ people's experiences in later life. Changes in cognitive function can jeopardize the safety, wellbeing, and human rights of LGBTQ+ people if the social care workforce are not prepared or versed in responding to their unique needs. The intersection of age, cognitive function, sexual and gender diversity with the expression of intimacy and sexuality requires sensitive and respectful consideration. Yet, this is currently an under-researched and less understood area in social care practice. This paper highlights the main messages from the different bodies of contributory literature and introduces the national framework in England UK on LGBTQ+ aging and its potential for supporting workforce development to consider its flexibility in supporting services to becoming more nuanced and affirmative in these areas of practice.